HR Leadership / Linda's Combination of Practical Example and Well-Argued Theory is a Powerful Mix - Holbeche Linda (Butterworth Heinemann, 2010)
This book draws on the personal experiences of some of today's most talented HR professionals who, through their leadership, are making a real difference to their organizations, no matter what industry they work in. Foreword, Acknowledgements, Introduction, The Time is Now, Who are the HR Leaders, Exercising HR Leadership, Leading for Strategic and Operational Excellence, Leading the Talent Agenda, Building Leadership Capability, Leading Change, Building Healthy and Ethical Organizations, Developing HR Leader Capabilities, The Future of HR?, References, Index.